Reflective and impulsive processes underlying saving behavior and the additional roles of self-control and habit. - Allom, Vanessa; Mullan, Barbara; Monds, L.; Orbell, S.; Hamilton, K.; Rebar, A.; Hagger, Martin (EDUCATIONAL PUBLISHING FOUNDATION-AMERICAN PSYCHOLOGICAL ASSOC, 2018)
© 2018 American Psychological Association. Using a dual-process framework, the aim of this research was to investigate the associations between reflective and impulsive processes and saving behavior. Self-control and saving habit were tested as additional factors that potentially moderate the relationship between constructs representing reflective and impulsive processes and behavior, or exert indirect effects on behavior through these systems. A community sample of 594 participants completed measures of saving intention, buying impulsiveness, trait self-control, saving automaticity, and propensity to save money. A well-fitting variance-based structural equation model, goodness-of-fit index = 0.338, average path coefficient =.119, p <.001, accounted for statistically significant amounts of variance in the key dependent variables: intention to save, R2 =.364, buying impulsiveness, R2 =.232, and saving behavior, R2 =.173. Self-control and saving habit were indirectly related to saving behavior through intention, and buying impulsiveness was directly related to behavior when saving habits were low. Findings indicate strong saving habits may help to protect against impulsive spending and offer several targets for interventions aimed at improving saving behavior.